Antioxidant activity of crude bromelain of pineapple (Ananas comosus (L.) Merr) crown from Subang district, Indonesia - Nyi M Saptarini; Driyanti Rahayu; Irma E Herawati (Wolters Kluwer Medknow Publications, 2019)
Background: Antioxidants are chemical compounds that can donate one or more electrons to free radicals to prevent degenerative diseases. The crown of pineapple (Ananas comosus (L.) Merr.) contains bromelain, that is, a proteolytic enzyme, which can act as an antioxidant. Aims and Objectives: The aim of this study was to determine the antioxidant activity of crude bromelain from pineapple crowns that were collected from Subang district, West Java, Indonesia. Materials and Methods: Antioxidant activity was determined by the method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) with vitamin C as a standard and measured with visible spectrophotometer. Results: The pineapple crown was produced 0.26% of dried crude bromelain with total protein content 44.10% and IC50 value 3624 μg/mL of crude bromelain, which was equivalent to 1590.18 μg/mL of total protein. Conclusion: Crude bromelain has medium antioxidant activity.